Investigation of redistribution of pile foundation forces under successive loading of its elements = Badania laboratoryjne redystrybucji sił w palach pod obciążeniem poszczególnych jego części - Sedin, Vladimir; Bikus, Kateryna; Kovba, Vladislav (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Redistribution of pile foundation forces under successive loading of its elements was investigated under laboratory conditions. A segment of pile foundation model was taken for use in the case study. Load tests on the pile foundation model segment, without joining its elements (pile and plate, which turns into grillage) and based on different combinations of static loadings were conducted.
Keywords: pile foundation; plate not joining a pile; additional friction; successive loading; laboratory test; fundament palowy; płyta; tarcie; obciążenia; badania laboratoryjne